Differences in Ocular Blood Flow in Glaucoma Between Patients of African and European Descent. Issue 2 (February 2015) - Siesky, Brent; Harris, Alon; Racette, Lyne; Abassi, Rania; Chandrasekhar, Kaarthik; Tobe, Leslie A.; Behzadi, Jennifer; Eckert, George; Amireskandari, Annahita; Muchnik, Michael
Abstract : Purpose: To investigate differences in ocular blood flow in individuals of African descent (AD) and European descent (ED) with open angle glaucoma (OAG). Patients and Methods: A retrospective data analysis was performed on OAG patients of AD and ED who were previously examined for ocular blood flow within the Department of Ophthalmology at Indiana University School of Medicine. Data analysis included blood pressure, heart rate, visual fields, intraocular pressure, ocular perfusion pressure, and color Doppler imaging of retrobulbar vessels. Color Doppler imaging measurements were performed on ophthalmic, central retinal, and nasal and temporal short posterior ciliary arteries, with peak systolic (PSV) and end diastolic velocities (EDV) as well as the Pourcelot vascular resistive index calculated for each vessel. Two-sample t tests of unequal variance were performed with P values <0.05 considered statistically significant. Results: OAG patients of AD had statistically significant lower retrobulbar blood flow values than patients of ED including lower ophthalmic artery PSV ( P =0.0001), ophthalmic artery EDV ( P =0.0008), central retinal artery PSV ( P =0.01), temporal short posterior ciliary artery PSV ( P =0.0037), and nasal short posterior ciliary artery PSV ( P <0.0001). No significant differences were found in terms of intraocular pressure or visual field parameters. Conclusions: Significantly lower blood flow values were identified in all retrobulbar blood vessels in AD compared with ED OAG patients. These findings suggest that the contribution of ocular blood flow to the disease process may be different in AD compared with ED OAG patients.